2021
DOI: 10.1186/s12884-021-04149-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth velocity references from a Chinese population–based fetal growth study

Abstract: Background Fetal growth velocity standards have yet to be established for the Chinese population. This study aimed to establish such standards suitable for the Chinese population. Methods We performed a multicenter, population–based longitudinal cohort study including 9075 low–risk singleton pregnant women. Data were collected from the clinical records of 24 hospitals in 18 provinces of China. Demographic characteristics, reproductive history, feta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Maternal glucose determinations have been linked to birth weight [ 3 ], and HbA1c levels found to have a linear relationship with infant size [ 9 ]. In addition, maximum fetal growth occurs in the second trimester [ 13 , 29 , 30 ]. These findings suggest that the fetal-placental unit consumes more glucose in the second trimester compared to the increase in maternal glucose production, leading to a decrease in HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal glucose determinations have been linked to birth weight [ 3 ], and HbA1c levels found to have a linear relationship with infant size [ 9 ]. In addition, maximum fetal growth occurs in the second trimester [ 13 , 29 , 30 ]. These findings suggest that the fetal-placental unit consumes more glucose in the second trimester compared to the increase in maternal glucose production, leading to a decrease in HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…Here again, an internationally curated database that includes access information, would justify and inform how FECs would be maintained, and valued based on analyzing the stakeholders that have access to them. Without doubt, these collections have value not only in providing population‐specific data on intrauterine growth and development (Keirse, 2000; Wu et al, 2021) that has the potential to improve healthcare and address the high mortality of infants globally, but also in the insight they provide in understanding the context of time and place in the history of medicine and of anatomy.…”
Section: Purpose: Why Were the Fecs Initiated And What Is Their Curre...mentioning
confidence: 99%
“…Fetal growth velocity varies with ethnicity 11,12 , and one study has demonstrated a different fetal-growth pattern in the Chinese population compared with other ethnic groups 13 . Moreover, maternal ethnicity influences the relationship between uteroplacental vascular insufficiency, as determined by UtA Doppler ultrasonography, and SGA.…”
Section: Introductionmentioning
confidence: 99%